The Personnel Administration According to the Four Sagahavatthu Principles by Educational Institution Administrators Under the Office of the Khon Kaen Primary Educational Service Area 1 - Thammasiri, Pasirat; Jotivungso, Phrakhrupalad Boonchuay; Techathammo, PhrakhruwinaithonWorawuth (Journal of Graduate MCU KhonKaen Campus, 2024)
This research aimed to 1) study personnel management according to the Four Sagahavatthu Principles by educational institution administrators under the Office of the Khon Kaen Primary Educational Service Area 1 and 2) propose guidelines for personnel management according to the Four Sagahavatthu Principles by educational institution administrators in the same area. This study used a mixed-methods approach, incorporating both quantitative and qualitative research. The quantitative aspect used a questionnaire with a reliability coefficient of 0.98, with a sample group of 305 school administrators and teachers. Data analysis methods included frequency, percentage, mean, and standard deviation. The qualitative aspect used a semi-structured interview with 9 key informants, chosen through purposive sampling, to validate data consistency and accuracy. The research results were as follows: 1. The state of personnel administration according to the Four Sagahavatthu Principles by educational institution administrators under the Office of the Khon Kaen Primary Educational Service Area 1, was generally at a high level. The highest to lowest ranked aspects were: Samnattat; Atthacariy; Dna and Piyavc. 2. The guidelines for personnel administration according to the Four Sagahavatthu Principles include: (1) school administrators should always demonstrate kindness to personnel and encourage them to pursue appropriate personal development. (2) Administrators should communicate with personnel in a polite, gentle, and neutral manner, avoiding bias, and respecting subordinates. (3) Administrators should use knowledge and judgment to establish systems for recruitment, task assignment, and performance evaluation that align with the school's needs. (4) Administrators should promote equitable welfare, distribute work and responsibilities fairly, and evaluate personnel with fairness and impartiality.